Impact of Flood Meso-Insurance on Agricultural Productivity: Evidence From Bangladesh - Mebada, Olivier (Université d'Ottawa | University of Ottawa, 2018)
Between 2012 and 2015, Oxfam Bangladesh launched a unique flood mese> insurance program across three districts of Bangladesh. Comparing differences in quantities harvested over time between the covered districts and a few compara ble non-covered districts, our results suggest that there is a substantial increase in quantities harvested in the areas where the flood insurance was put into place. We were able to estimate the average increase in quantities harvested of approximately 4% after the flood insurance program was implemented in the covered districts.